Characterization of naturally occurring severe combined immunodeficiency (SCID) in a line of pigs and their response to porcine reproductive and respiratory syndrome virus (PRRSV) infection - Cino-Ozuna, Ada Giselle (Kansas State University, 2016)
Severe combined immunodeficiency (SCID) is a rare group of inherited disorders characterized by defects in both humoral and cellular immune functions. Naturally occurring SCID has been first described in humans in the 1960s and subsequently identified in horses, mice, and dogs, but never before in pigs. Affected animals are characterized by having loss of functional B and T lymphocytes, and in some cases natural killer (NK) cells, but normal numbers of monocytes, granulocytes, and megakaryocytes. As a result, affected animals fail to produce antibodies and succumb to common disease pathogens after circulating maternal antibodies decay. SCID models are extremely valuable for the understanding of molecular mechanisms of immunological processes during viral and bacterial diseases, cancer, and autoimmunity. SCID mice are widely used as the current model; however, the relevance of the murine SCID model to human and veterinary immune research is limited and there is an increasing need for a more representative model of SCID is imperative. We describe the gross, microscopic, and immunophenotypic characteristics of a line of Yorkshire pigs having naturally occurring SCID. Affected pigs lack T and B lymphocytes, but display circulating NK cells, fail to produce antibodies to viral infection, and lack cell-mediated response to tumor xenotransplants. We also describe response of SCID pigs to porcine reproductive and respiratory syndrome virus (PRRSV). PRRSV is the most devastating virus in swine industry, causing losses of billions of dollars annually. Understanding the immunopathogenesis of the disease is imperative in order to develop strategies to combat this devastating virus. PRRSV infected-SCID pigs failed to develop lesions of PRRSV infection, demonstrating the significant role of the adaptive immunity to PRRSV infection. Finally, we describe the preliminary results of the adoptive transfer of purified CD3⁺ T lymphocytes to SCID pigs from SLA-II matched wild-type littermates, with the objective of establishing a porcine model for the study of T cell immunopathogenesis with viral diseases.
Keywords: Porcine; Primary immunodeficiency; Severe combined immunodeficiency; Porcine reproductive and respiratory syndrome virus; Veterinary medicine; Immunology